Electronic Certificate Information System as Media for Distributing Certificates Online During the Covid-19 Pandemic - Suwita, Ferry Stephanus (Universitas Komputer Indonesia, 2023)
Pandemic is a challenge for all people in the world. Enforcing social distancing is a challenge in itself when it comes to holding face-to-face activities. The use of online media to hold face-to-face activities has become very common during this pandemic. Several institutions use this online media to hold useful activities during the pandemic. In every activity, the institution usually provides a certificate as proof of participation. However, this becomes an obstacle in distributing the certificate itself. With this online certificate information system, it is hoped that it can answer this problem. This online certificate information system makes it easy for the committee to distribute certificates with a QR code to validate the authenticity of the certificate